STRATEGI PENGEMBANGAN USAHA JASA LAUNDRY SEPATU DI KOTA PEKANBARU - Fathoni Muhammad; Harahap Azwar; Indrawati Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The shoe laundry service business is a service needed by the community. This research aims to find out how the strategy for developing a shoe laundry service business in Pekanbaru City. Research location was carried out in all shoe laundry service businesses in Pekanbaru City with a total sample of 13 businesses. Types of data sources used are primary data and secondary data. The data analysis method used was SWOT analysis and formulated strategies with IFAS and EFAS matrix analysis. The result of this research is that the shoe laundry service business in the city of Pekanbaru is in quadrant 2 (Diversification). The strategy that needs to be applied is ST (strength-treaths), this strategy is made by using the strengths of the business to overcome treaths. In this result, the shoe laundry service business, although facing various threats, still has strength from an internal perspective. On the IFAS matrix (0.24) and on the EFAS matrix (-1.30). ST strategies that need to be implemented include: 1. Good sales ability will certainly have an impact on product specialization, 2. Having good service quality can overcome difficulties in determining market prices.Keywords: Strategic, shoe laundry service business, SWOT